Minimally invasive thoracoscopic surgery is an effective approach for treating inappropriate sinus tachycardia. (20th June 2019) - Aalaei‐Andabili, Seyed Hossein; Miles, William M.; Burkart, Thomas A.; Panna, Mark E.; Conti, Jamie B.; McKillop, Matthew S.; Beaver, Thomas M
Abstract: Introduction: Inappropriate sinus tachycardia (IST) is characterized by increased heart rate out of proportion to normal physiologic demand. IST ablation is challenging for the electrophysiology community due to the epicardial location of the sinus node and the risk of phrenic nerve (PN) injury during catheter ablation. In this study, we investigated the safety and efficacy of a minimally invasive thoracoscopic surgery for elimination of IST. Methods: Patients with IST who failed medical therapy or endocardial ablation underwent minimally invasive thoracoscopic epicardial ablation. Epicardial activation mapping was performed to identify the earliest activation site and any possible migration of earliest activation along the lateral right atrium. The PN in each patient was protected by a pericardial retraction suture. Results: From 1 January 2000 to 15 June 2018, 10 patients (eight females and two males) underwent minimally invasive thoracoscopic IST ablation. Mean age of the patients was 36.7 ± 12.5 years. Mean baseline sinus rate was 113.8 ± 21.8 beats per minute. After surgery, the mean heart rate significantly decreased to 79.8 ± 8.2 at postoperative day 1 and to 75.8 ± 8.1 at day 30 (both P < .001). No in‐hospital death, stroke, or PN injury occurred. One patient required reintubation, one patient developed postoperative pericarditis, and another patient had a pulmonary embolus. Median follow‐up was 6 months (range, 1‐50). Freedom from reintervention was 88% at 6 months. Conclusion: Minimally invasive thoracoscopic ablation for IST is a safe and effective approach that preserves the phrenic nerve. Due to the possibility of IST activation site migration, continued follow‐up after surgery is required.